2011
DOI: 10.1002/we.481
|View full text |Cite
|
Sign up to set email alerts
|

Modeling wake effects in large wind farms in complex terrain: the problem, the methods and the issues

Abstract: Computational fluid dynamic (CFD) methods are used in this paper to predict the power production from entire wind farms in complex terrain and to shed some light into the wake flow patterns. Two full three‐dimensional Navier–Stokes solvers for incompressible fluid flow, employing k − ϵ and k − ω turbulence closures, are used. The wind turbines are modeled as momentum absorbers by means of their thrust coefficient through the actuator disk approach. Alternative methods for estimating the reference wind speed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 13 publications
(27 reference statements)
2
83
0
2
Order By: Relevance
“…(4) is used. However, in (Ishihara et al, 2004;Mittal et al, 2011;Politis et al, 2011) it is demonstrated that this equation is not so reliable because only the ambient turbulence level is considered. In fact, the wake decay is influenced by a lot of factors.…”
Section: Wake Turbulence Modelmentioning
confidence: 99%
“…(4) is used. However, in (Ishihara et al, 2004;Mittal et al, 2011;Politis et al, 2011) it is demonstrated that this equation is not so reliable because only the ambient turbulence level is considered. In fact, the wake decay is influenced by a lot of factors.…”
Section: Wake Turbulence Modelmentioning
confidence: 99%
“…There has been considerable research into optimising the power output of a wind farm via the placement of the wind turbines themselves (Chowdhury et al 2012;González et al 2011;Husien et al 2013;Magnusson & Smedman 1999;Meyers & Meneveau 2012;Politis et al 2012;Røkenes & Krogstad 2009) and most notably the work carried out from Risø National Laboratories in Denmark on the European Wind Atlas, providing comprehensive wind statistics (Troen & Petersen 1989). The issue of wind turbine siting is important for overall energy yield and relies heavily on how each turbine is placed with respect to its surroundings and more importantly, other turbines.…”
Section: Energy Yield As a Developer Responsibilitymentioning
confidence: 99%
“…Once the model has proved to be valid for an isolated wake case, a first result is obtained for a small wind farm like the ECN test farm [17][18][19], located at flat coastal terrain and composed by 5 wind turbines Nordex N80 of 2.5 MW in a row. Separation between wind turbines is 3.8D.…”
Section: Validation At the Ecn Test Farmmentioning
confidence: 99%